Knowledge and Beliefs of Informal Caregivers of Children with Cerebral Palsy in Nigeria Concerning Cerebral palsy (2019)
Background: Caregivers of children with Cerebral Palsy (CP) play an important role in the habilitation of their wards. Their knowledge and beliefs about CP may affect their disposition to habilitation and the quality of care and habilitation their wards would receive. Knowledge and beliefs of informal caregivers of children with CP in Southwest, Nigeria were investigated in this study. 3 six(71%) respondents reported good knowledge while 9(9.7%) reported poor knowledge about cerebral palsy. Most of the caregivers responded correctly in expressing their belief, causes and management of cerebral palsy Methods: Ninety-three informal caregivers (relatives or friends) of children with CP who routinely provide an average of 3-5hours of care per week without pay were surveyed. A 56-item questionnaire was used to collect information on socio-demographics, knowledge and beliefs of the informal caregivers about CP. Data were summarized using descriptive statistics of mean, percentages and standard deviation. Results: Participants were aged 36.6 ±8.6 years and their age ranged from 16-66 years. Majority of the respondents (n = 85; 91.4%) were female. Most of the participants (n = 87; 93.5%) were married and (62.4%) had completed tertiary education. Sixty six (71%) respondents reported good knowledge while 9(9.7%) reported poor knowledge about cerebral palsy. Most of the caregivers responded correctly in expressing their belief, causes and management of cerebral palsy Conclusions: Informal caregivers of children with cerebral palsy in southwestern Nigeria had good knowledge and positive beliefs about cerebral palsy hence the need to ensure that they seek appropriate intervention to this condition.